Cat Ballou - Elliot Silverstein; Dwayne Hickman; Lee Marvin; Michael Callan; Nat 'King' Cole; Stubby Kaye; Tom Nardini; Jane Fonda (USA Columbia Pictures Corporation, 1965)
Cat(herine) Balou's family farm is being threatened by the Rail Road. She sends for Kid Shelleen, finding him to be the drunkest gunfighter in the west. When her father is killed by the rail road magnate's gunman, she vowes to fight on. Shelleen manages to ride sideways in several scenes, while minstrels sing the ballad of Cat Ballou in between scenes.
A woman seeking revenge for her murdered father hires a famous gunman, but he's very different from what she expects.
Roy Chanslor
Language(s): English, German
Subtitle(s): English, German, Hindi, Turkish
Keywords: Western; Comedy